SEMANTIC ANALYSIS OF SOMATIC COMBINATIONS IN UTKIR HOSHIMOV’S "BETWEEN TWO DOORS". - Gadoyeva, Mavlyuda (Центр Научных Публикаций (buxdu.uz), 2024)
This article is aimed to analyze the meaning of somatisms which are used in Utkir Hoshimov’s work "Between Two Doors". Furthermore, it expresses the meaning of somatic units within the framework of this work. In addition, the article discusses the types of somatisms and their use in linguistics. Of course, the importance of somatic phraseological units is also highlighted with the clear examples in the process of discussion.